FACTORS CONTRIBUTED TOWARD STUNTING IN CHILDREN IN INDONESIA - Anggraeni, Lina Dewi; Utami, Tuti Asrianti; Wihardja, Hany (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2025)
Stunting is a condition of failure to thrive in children under five due to chronic malnutrition, especially in the first 1000 days of Life. Stunting is closely related to the growth and development of the brain and the risk of suffering from chronic diseases in adulthood. Multi-factors that caused stunting include nutrition intake, toddler health status, maternal characteristics, parity, breastfeeding history, and the environment sanitation. This study aimed to identify the factors associated with the incidences of stunting in children under five years. This study was a quantitative study with a cross-sectional approach. This study was conducted from April to October 2019. This study involved 220 toddlers aged 1-5 years with their mothers. Study revealed that number of children were statistically correlated with to the incidence of stunting (p-value 0.005). There were three factors associated with the incidence of stunting in children under five years of age These factors are parity, history of exclusive breastfeeding, and mother's knowledge. The parity factor or the number of children is the most related factor with the incidence of stunting in children (p-value 0.007). Mothers of toddlers must be motivated to provide adequate nutrition in accordance with the needs at the age of growth and development. Government programs to overcome stunting need to start from family planning and the quality of performance of nutrition programs, one of which is intensive nutrition education for pregnant women and mothers of toddlers.